Penetapan Standar Warna Daun Sebagai Upaya Identifikasi Status Hara (N) Tanaman Jagung (Zea mays L.) pada Tanah Regosol - Nugroho, Wisnu Sapto (Universitas Muhammadiyah Yogyakarta, 2015)
A study aims to determine a standard of green color on corn leaves as marker of nitrogen adequacy. A study was conducted in the field of Universitas Muhammadiyah Yogyakarta. The experiment was arranged in a completely randomized design (CRD, which consisted of 7 treatments: 125 kg N/h (N1), 150 kg N/h (N2), 175 kg N/h (N3), 200 kg N/h (N4), 225 kg N/h (N5), 250 kg N/h (N6), and 275 kg N/h (N7). The result showed that the scale between 5GY 5/8 and 5GY 6/8 was the best Leaf color scale to identify Nitrogen condition on corn yield at range of 250 kg N/h and 275 kg N/h. The dose of 250 kg N/h resulted the highest plant height of corn. The dose of 275 kg N/h resulted the highest seed weight per ear and grain weight of 100 seeds at 14% moisture content.